(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
In the penal code it was established that it cannot be punished who was deprived of the capacity to understand and to want at the time of the commission of the offence and it was stated that the inability of the defendant must always be provoked by an infirmity. In 2005 the Court of Cassation clarified that also personality disorders can be detected for imputability purposes. Starting from that year the judge is therefore called toascertain the imputability also of person suffering from a personality disorder and, to this end, it makes use often of the collaboration of the neuro-scientists. This collaboration allows him, in fact, to assess the infirmity of the offender on a more scientific basis and to under standwhether the same infirmity has been decisive for the commission of the offence.